بيان المعاني في سورة محمد: دراسة تحليلية - الزعاقي، وفاء بنت عبدالله بن عبدالعزيز (جامعة الأزهر - كلية الدراسات الإسلامية والعربية للبنات بدمنهور, 2022)
موضوع البحث: تناولت الدراسة موضوع (بيان معاني في سورة محمد دراسة تحليلية) أهداف البحث: وتهدف إلى التعرف على خصائص بيان المعاني في سورة مُحَمَّد، وتوظيف علوم السورة في بيان معانيها والكشف عن بيان المعاني في السورة اللفظية وغير اللفظية. منهج البحث: المنهج التحليلي الاستنباطي. النتائج: تنوع أساليب بيان المعنى في سورة محمد بين اللفظي وغير اللفظي. وعلوم السورة مصدر من مصادر دراسة معانيها. بيان المعاني هو إظهار المعاني التي دلت عليه الأساليب اللفظية وغير اللفظية في السورة. من أساليب بيان المعاني اللفظي في السورة البيان أسلوب التعبير بالضمائر واسم الموصول واسم الإشارة والتعبير بالتكرار وبالجمل المركبة وبالتقابل بين الألفاظ ودلالتها. من أساليب بيان المعاني غير اللفظي البيان بذكر السبب، والبيان بالعموم. التوصيات: دراسة أساليب بيان المعاني في سورة محمد وإيراد جميع الأمثلة عليها. العناية بأساليب بيان المعاني في القرآن الكريم وفق معنى بيان المعاني في الدراسات القرآنية. دراسة العلاقة بين الفاصلة القرآنية ومعنى الآية الكريمة. ربط علوم السورة بدراسة معانيها. Thesis: The study touches on (Interpretation of Meanings in Surah Muhammad: an Analytical Study) Objectives: The study indents to identify the characteristics of interpretation of meanings in Surah Muhammad. It further intends to draw on particulars of the Surah for interpreting its meanings and revealing the verbal and non-verbal meaning interpretation methods in the Surah. Approach: Deductive Analytical Approach. Findings: The diverse methods for interpretation of the meanings in Surah Muhammad (i.e. verbal and non-verbal). The particulars of Surah is a source for study of its meanings. Interpretation of meanings is to explain the meanings indicated by the Surah’s verbal and non-verbal methods. The verbal meaning interpretation methods include the use of pronouns, relative nouns, demonstrative pronouns, repetition, compound sentences, and antonym and its significance. The non-verbal meaning interpretation methods include expression by stating the reason, and the interpretation in general. Recommendations: Studying the methods of interpretation of the meanings in Surah Muhammad and setting out all relevant examples and paying attention to the methods of interpretation of the meanings in Qur’an according to meaning of the meaning interpretation in Qur’an-related studies. Studying relationship between the Quranic pauses and meaning of the verse and linking particulars of the Surah to the study of its meanings.
Keywords: القرآن الكريم -- سورة محمد -- البيان اللفظي -- المعاني اللغوية